KINERJA PUSAT MISI PEMELIHARAAN PERDAMAIAN TNI DALAM PENYIAPAN KEMAMPUAN PRAJURIT TNI GUNA MISI PERDAMAIAN DUNIA (Studi di Pusat Misi Pemeliharaan Perdamaian/PMPP TNI) - , I Gede Sumertha Kusuma ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is aiming to find out more about the Indonesian National Defense Forces Peacekeeping Center and its performance in preparing soldiers for the mission capability of peacekeeping operation under the flag of the United Nations (UN). Research conducted with qualitative methods which emphasize the collection and analysis of written texts (literature study) and expression (statements, interviews and discussions). Since the end of the cold war, the government point of view of developed countries and third world has changed in the face of the global situation and give more serious attention to the implementation of peacekeeping missions. Indonesia as a sovereign state and has the potential, seeking to increase its contribution in the peacekeeping mission. For that, in response to this challenge, the Government of Indonesia through the military has established a Peacekeeping Centre (PMPP TNI), in order to deal with all issues relating to peacekeeping missions in a more focused and professional. PMPP TNIâs role is not only select personnel are eligible through recruitment system that professionally, but also serves to enhance the ability of military personnel through training programs that are designed to address operational needs in the face of the complexity of the current peacekeeping mission and future. Intensify the dialogue established through cooperation with regional peacekeeping center and relevant organizations can also improve the capability and reduce the gap of understanding, coordination and cooperation in implementing an integrated, on operational and tactical levels, so as to answer the dynamics of the field effectively. One of the toughest challenges PMPP TNI is to train and prepare ability TNI soldiers, which was originally formed as a fighter, but then must be able to carry out the mission of peacekeeping operation under the flag of the United Nations as a Peacekeeper. In order to meet this task, it is appropriate if the PMPP TNI has the discretion to conduct direct coordination and cooperation with other countries Peacekeeping Centre. Due to exchange information and experience, it's easier to find the standard capabilities that are expected by the UN. With the establishment of PMPP TNI as the front guard in dealing with peacekeeping missions, it is believed that extending opportunities will be optimized for decision-making process becomes more rapid, effective and efficient.